CREATIVITY ISSUES IN THE FORMATION OF THE FUSION SKILLS OF FUTURE MUSIC TEACHERS (American Journal of Pedagogical and Educational Research, 2023)
The article is devoted to the definition of actual problems of professional training of music teachers. The author conducts a critical analysis of scientific research of various directions and determines ways to improve the training of future teachers-musicians. In the first direction, the implementation of modern approaches in teaching students – integrated, integrated and interactive - is considered.